Mo1.33CTz–Ti3C2Tz mixed MXene freestanding films for zinc-ion hybrid supercapacitors. (December 2021) - Etman, Ahmed S.; Halim, Joseph; Rosen, Johanna
Abstract: The high demand on fast rechargeable batteries and supercapacitors combined with the limited resources of their active materials (e.g. Li and Co) motivate the exploration of sustainable energy storage systems such as Zn-ion hybrid supercapacitors. MXenes are two-dimensional materials with outstanding properties such as high conductivity and capacitance which enhance their performance in energy storage devices. Herein, we report on the use of freestanding Mo1.33 CTz –Ti3 C2 Tz mixed MXene films in Zn-ion hybrid supercapacitors. The mixed MXene films are prepared from pristine MXene suspensions using a one-step vacuum filtration approach. The mixed MXene delivers capacities of about 159 and 59 mAh/g at scan rates of 0.5 and 100 mV/s, respectively. These capacity values are higher than the pristine MXene films and previously reported values for MXene electrodes in Zn-ion supercapacitors. Furthermore, the electrodes offer a promising capacity retention of about 90% after 8, 000 cycles. In addition, the mixed MXene features energy densities of about 103 and 38 Wh/kg at power densities of 0.143 and 10.6 kW/kg, respectively. Insights into the effect of electrode thickness on rate performance and the mechanism of charge storage are also discussed. This study opens a venue for the use of Mo1.33 CTz –Ti3 C2 Tz mixed MXene electrodes in sustainable energy storage systems with high energy density and power density. Graphical abstract: Image 1 Highlights: The mixed MXene delivers capacities of about 159 and 59 mAh/g at scan rates of 0.5 and 100 mV/s, respectively. The mixed MXene electrodes offered a promising capacity retention of about 90% after 8, 000 cycles. The films feature energy densities of about 103 and 38 Wh/kg at power densities of 0.143 and 10.6 kW/kg, respectively. Insights into the effect of electrode thickness on rate performance and the mechanism of charge storage are also discussed.